(untitled) (Proceedings of the International Conference on Public Health, 2019)
Adherence to Methadone Maintenance Treatment (MMT) is one of evaluation criterias in MMT because it requires a long period of therapy. Adherence pattern and related factors are important to achieve treatment goals. This study aimed to identify several factors related to MMT adherence in West Java, Indonesia. This cross-sectional study was carried out on 94 participants from three selected primary health cares which conduct MMT program in West Java in 2018. Data was collected from patients interview, methadone retrieval records from last 30 days, and medical records. Analysis was performed using multivariate logistic regression. Participants in the age group 35-56 years were 83.7%, most of them were male (89.1%), and 65.2% were married. Total of 58.7% participants were adherent. Having history of HIV positive [adjusted odd ratio (ORa) = 4.03; P = 0.005] and presence of person who can share with (ORa = 6.26; P = 0.005) were significant related factors for higher adherence. Adherence to MMT was associated with several factors. To improve patient’s adherence, support from family and friends are required. Meanwhile, patients with history of negative HIV must be monitored to sustain patients’ adherence to MMT program.